Othering as soft-power discursive practice: China Daily's construction of Trump's America in the 2016 presidential election. (February 2020) - Pan, Chengxin; Isakhan, Benjamin; Nwokora, Zim
The relationship between Chinese soft power and Chinese media has been a focus of a growing body of literature. Challenging a resource-based conception of soft power and a transmission view of communication that inform much of the debate, this article adopts a discursive approach to soft power and media communication. It argues that their relationship is not just a matter of resource transmission, but one of discursive construction, which begs the questions of what mediated discursive practices are at play in soft power construction and how. Addressing these oft-neglected questions, we identify a typology of three soft-power discursive practices: charm offensive, Othering offensive, and defensive denial. Focusing on the little-understood practice of Othering offensive, we illustrate its presence in Chinese media through a critical discourse analysis of China Daily 's framing of Donald Trump and the United States, and argue that the Othering offensive in Chinese media that portrays Trump's America as a dysfunctional and declining Other serves to construct a Chinese self as more responsible, dynamic, and attractive. Adding a missing discursive dimension to the study of soft power and the media, this study has both scholarly and practical implications for analysing a nation's soft power strategy.